Transformation of Snakes and Ladders through Index Card Match: Educational Media to Improve Early Childhood Cognition - Syofiyanti, Dessy; Susanti, Pipit Aprilia; Cahyani, Nur; Hasnida, Hasnida (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
Early childhood cognitive development is a critical foundation for future learning. However, many existing learning methods remain monotonous and less engaging, leading to low participation and slow cognitive progress among children. To address this, interactive and enjoyable learning media is essential. This study aims to improve early childhood cognitive development through the transformation of the traditional snakes and ladders game integrated with the Index Card Match (ICM) method. The game was selected for its ability to stimulate recognition of basic symbols—numbers, letters, colors, shapes, and sizes—which are key elements in early cognition. The research was conducted at Ceria Eduloka Kindergarten, Seberida District, using a participatory Classroom Action Research (CAR) design consisting of planning, implementation, observation, and reflection in two cycles. The game was modified by adding ICM elements, where children match questions and answers during each move, promoting active thinking and engagement. Data were collected through observation, teacher interviews, and documentation. The results showed a significant increase in cognitive achievement, with average scores rising from 33% in the pre-cycle to 86% in the second cycle. This indicates that the modified game successfully fosters basic cognitive abilities such as recognition, understanding, and problem-solving. Theoretically, the study contributes to the application of constructivist learning and multimodal approaches in early childhood education. In the long term, this educational media has the potential to be replicated in various early childhood education settings as an inclusive, engaging, and culturally adaptive tool to support the development of cognitive and social-emotional competencies in young children.